2022
DOI: 10.3390/plants11233222
|View full text |Cite
|
Sign up to set email alerts
|

The LC-MS/MS Identification and Analgesic and Wound Healing Activities of Lavandula officinalis Chaix: In Vivo and In Silico Approaches

Abstract: We earlier emphasized in vivo the lavender plant’s (Lavandula officinalis Chaix.) anti-inflammatory and estrogenic activities and described the chemical compositions of its hydro-ethanolic (HE) extract. We used LC-MS/MS and GC-MS analyses to profile the phytochemical composition of the HE extract and to assess the analgesic and wound-healing effects of both the hydro-ethanolic (HE) and polyphenolic (LOP) extracts in vivo and in silico. The analgesic activity was studied using two methods: acetic acid and forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The molecular docking of Lavandula officinalis phytocompounds showed a glide score energy between −4.596 and −5.34 kcal/mol in the active site of casein kinase-1, and a glide score energy between −6.298 and −7.652 kcal/mol in the active site of glycogen synthase kinase-3β [ 29 ]. Another study targeted CK1 in the same active site, hence the importance of this active site to target this protein [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular docking of Lavandula officinalis phytocompounds showed a glide score energy between −4.596 and −5.34 kcal/mol in the active site of casein kinase-1, and a glide score energy between −6.298 and −7.652 kcal/mol in the active site of glycogen synthase kinase-3β [ 29 ]. Another study targeted CK1 in the same active site, hence the importance of this active site to target this protein [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This site is crucial for the catalytic activity of COX-2. A previous study targeted the same active site of cyclooxygenase-2 studied in our research; in this active site, Lavandula officinalis molecules showed a glide score energy of −6.156 and −7.526 kcal/mol [ 29 ]. Other studies used the same residue-limited active site to evaluate phytochemicals derived from Holigarna caustica (Dennst.)…”
Section: Discussionmentioning
confidence: 99%
“…According to the protocol of Heidari et al, (2019), after anesthesia of rats with pentobarbital (50 mg/kg) and shaving the dorsal part with an electric clipper [ 52 ], the induction of the burn was carried out on the shaved part using an aluminum rod (1.7 cm) heated to 110 °C for 10 s. After 24 h, the treatment was started by applying the ointments to the burned zones for 25 days while photographing the healing progress using a digital camera and the ruler used as a scale. ImageJ ® software was used to analyze the images and measure the rate of wound contraction using the following formula [ 53 ]: WC (%) = Rate of wound contraction. WS 0 = Size of the wound at the first day.…”
Section: Methodsmentioning
confidence: 99%
“…The three-dimensional structure of 5-Lipoxygenase (PDB ID: 3V99) was used to assess anti-inflammatory activity [29], cyclooxygenase-2 (prostaglandin synthase-2) (PDB ID: 6COX) to assess antinociceptive activity [30], and crystal structure of human casein kinase 1 (PDB ID: 6GZD) and crystal structure of glycogen synthase kinase 3 (PDB ID: 1Q5K) to evaluate wound healing activity [31]. These structures were directly sourced from the protein data bank.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…In wound healing, the Wnt/β-catenin signaling pathway is crucial and involves several proteins, including glycogen synthase kinase-3β (GSK-3β) and casein kinase-1 (CK1) [30]. Benzenepropanoic acid and delta-9-Tetrahydrocannabivarin were the most active molecules against Casein Kinase 1 with a glide score of −5.540 and −4.741 kcal/mol.…”
Section: Amcanamentioning
confidence: 99%